On the complexity of IgE: The role of structural flexibility and glycosylation for binding its receptors - Plattner, Kevin; Bachmann, Martin F.; Vogel, Monique (Frontiers in Allergy, 2023)
It is well established that immunoglobulin E (IgE) plays a crucial role in atopy by binding to two types of Fcε receptors (FcεRI and FcεRII, also known as CD23). The cross-linking of FcεRI-bound IgE on effector cells, such as basophils and mast cells, initiates the allergic response. Conversely, the binding of IgE to CD23 modulates IgE serum levels and antigen presentation. In addition to binding to FcεRs, IgE can also interact with other receptors, such as certain galectins and, in mice, some FcγRs. The binding strength of IgE to its receptors is affected by its valency and glycosylation. While FcεRI shows reduced binding to IgE immune complexes (IgE-ICs), the binding to CD23 is enhanced. There is no evidence that galectins bind IgE-ICs. On the other hand, IgE glycosylation plays a crucial role in the binding to FcεRI and galectins, whereas the binding to CD23 seems to be independent of glycosylation. In this review, we will focus on receptors that bind to IgE and examine how the glycosylation and complexation of IgE impact their binding.